Numerical simulation of the influencing factors of array jet shock cooling - Zhou, Nianyong; Zhou, Youxin; Zhao, Yingjie; Bao, Qingguo; Tang, Guanghua; Lv, Wenyu (Bulletin of the Polish Academy of Sciences Technical Sciences, 2024)
Array jet impingement cooling is a significant technology of enhanced heat dissipation which is fit for high heat flux flow with large area. It is gradually applied to the cooling of electronic devices. However, The research on the nozzle array mode and the uniformity of the cooling surface still has deficiencies. Therefore, the influence of heat flux, inlet temperature, jet height, array mode, and diversion structure on jet impingement cooling performance and temperature distribution uniformity is analyzed through numerical calculation. The results show that the heat transfer coefficient of jet impingement cooling increases linearly with the increment of heat flux and inlet temperature. With the increment of the ratio of jet height to nozzle diameter (H/d), the heat transfer coefficient increases first and then decreases, that is, there is an optimal H/d, which makes the heat transfer performance of the array jet impact cooling best. The temperature uniformity of array jet impact cooling is greatly affected by array mode. The improvement effect of nozzle array mode on temperature uniformity is ranked as sequential >staggered >shield >elliptical array. The overall temperature uniformity and heat transfer coefficient are increased by 5.88% and 7.29% compared with the elliptical array. The heat transfer performance can be further improved by adding a flow channel to the in-line array layout, in which the heat transfer coefficient is increased by 6.53% and the overall temperature uniformity is increased by 1.45%.